Changing Workplace Relations and Sites of Belonging in Swedish University Administration - Öborn, David Regin (Nordic Journal of Working Life Studies, 2024)
Based on a mixed-methods case study, this article explores the impact of formal affiliations and informal associations in professional organizations, relating these questions of belonging to workplace dynamics and collectives. Using the experience of departmental administrators within a Swedish university as an ideal case to investigate the formal and informal connections at work, this article argues that a multiplicity of belongings within organizations brings strain and opportunities, altering the relations at work. The study contributes to discussions on belonging and social relationships at the workplace level by applying the concept of belonging to different sites in the organization. It suggests that sites of belongings within organizations can serve as a discrete concept, useful for adding insights into the dynamics of work organizations.